Platinum-group elements (PGE), Re, Ni, Cu, Ag and Cd variations along the Reykjanes Ridge and Iceland South-West Neovolcanic Rift Zone, from 50°N to 65°N: Implications on sulfide bearing PGE mantle source heterogeneities and partial melting effects ... - Schilling, Jean-Guy; Kingsley, Richard (Interdisciplinary Earth Data Alliance (IEDA), 2017)
We report on the concentrations of platinum group elements (PGE), Re, Ag and Cd in 53 tholeiitic basalts and one picrite from the Reykjanes Ridge and its extension over Iceland. The purpose is to investigate sulfide bearing PGE mantle source heterogeneities and partial melting effects. Included is: 1) Supplementary information on the PGE Analytical Method used, and 2) a PGE multi inter-laboratory comparison on the URI EN26 10D-3 MORB reference standard ... : Jean-Guy Schilling and Richard H. Kingsley, 2017, Platinum-group elements (PGE), Re, Ni, Cu, Ag and Cd variations along the Reykjanes Ridge and Iceland South-West Neovolcanic Rift Zone, from 50°N to 65°N: Implications on sulfide bearing PGE mantle source heterogeneities and partial melting effects. Research Gate/Schilling, Working Paper, 21 pages ...